DIAGNOSTIC VALUE OF POLYMERASE CHAIN REACTION FOR THE RAPID DIAGNOSIS OF CLINICALLY SUSPECTED TUBERCULOUS MENINGITIS - USHARANI BRAMMACHARRY; MUTHAIAH MUTHURAJ (International Journal of Pharma and Bio Sciences, 2014)
To study the efficiency of Polymerase Chain Reaction for the diagnosis of clinically suspected tuberculous meningitis, a rapid molecular technique was established. The conventional bacteriological methods rarely detect Mycobacterium tuberculosis in CSF and are of limited use in diagnosis of tuberculous meningitis (TBM). This double blind study was, therefore, directed to the molecular analysis of CNS tuberculosis by PCR targeted for amplification of 123bp nucleotide sequence coding IS6110 insertion element. In this study, the efficiency of the Polymerase Chain Reaction (PCR), one of the most reliable and sensitive DNA-based assays, was compared with conventional Microscopy and Solid culture for the detection of M.tuberculosis in cerebrospinal fluid specimens from patients suspected of TBM. Of the 69 CSF specimens from highly-probable TBM patients based on clinical features, 51 were positive by PCR (78.46%), whereas microscopy and culture results were negative. Thus, PCR was found to be more sensitive than any other conventional method in the diagnosis of clinically suspected tubercular meningitis.